Organisational ventriloquism in a project centered organization: a qualitative inquiry into the effects of ritualized mimeticisomorphism within a project centered organization - Steyn, Keegan (GSB: Faculty, 2016)
The management of projects has been area of intense study for many years, yet few researchers have ventured outside parameters of the mainstream concerns. This research aims to move outside the parameters of mainstream project management research, in order to explore other perspectives, with the purpose of illuminating new concerns and agendas. An abductive research strategy within a single case study was utilized to obtain rich data and new insights. This research seeks to uncover the social forces that influence the adoption of mainstream project and programme management standards and structures. The literature revealed that mainstream project management has idealogical foundations rooted within a 'Cartesian-Taylorist' paradigm and these have affected the development of programme management. The empirical findings indicated that a superficial understanding existed regarding the motivation for the adoption of project management standards and structures, within the case company. In addition, it was noted that the adoption of these project management standards and structures was perceived to provide more control and legitimacy. A consequence of these practices, within the case organization, is that it created a strong resource dependence on external consultants. The theoretical explanations illuminated that the desire for control, reducing uncertainty and the need for competitiveness serve as social forces towards the adoption of mainstream project and programme management standards and structures. Furthermore, the research explored the consequences of this phenomenon, within the case organisation.